Recurrent stroke in a young man with Moyamoya Disease on medical therapy: a case report / Nurfauzani Ibrahim ... [et al.] - Ibrahim, Nurfauzani; Baharudin, Noorhida; Hashim, Hilwati; Jaya Raman, Thinesh Kumaran; Mohamed-Yassin, Mohamed-Syarif (Faculty of Medicine, 2022)
Moyamoya disease (MMD) is a rare intracranial vasculopathy characterized by the progressive occlusion of the terminal internal carotid arteries and their proximal branches. Various factors including genetic and inflammation are the proposed pathogenesis of MMD. We present a case of a 31-year-old man who had recurrent stroke secondary to MMD. Magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) demonstrated an infarct in the right middle cerebral artery (MCA) territory, and stenosis of the terminal right internal carotid artery (ICA) and its proximal branches. He initially declined surgical management and was treated with antiplatelet. After his third stroke, he finally underwent right superficial temporal artery (STA) to middle cerebral artery (MCA) bypass surgery. He improved following rehabilitation with no further recurrence. The role of surgical revascularization in the prevention of stroke is well-described in the literature but evidence regarding medical therapy remain scarce and will be explored in this report.